Evolution of chemical and mechanical properties in two-photon polymerized materials during pyrolysis. (May 2023) - Mao, Aofei; Mitsuboshi, Hibiki; Trochon, Maxime; Zhang, Xiang; Trinh, Lanh; Keynia, Sedighe; Fan, Peixun; Kraiem, Nada; Huang, Xi; Li, Nan; Li, Peizi; Wu, Zhipeng; et al.
Abstract: Fabrication of three-dimensional (3D) carbon-based structures at micro/nanoscale, mainly by pyrolysis of photocured resins, has recently drawn attention in battery development, material engineering, and catalysts. Upon pyrolysis, photocured 3D polymer structures undergo thermal decomposition and eventually carbonize while maintaining their 3D features. Herein, we systemically investigate the physical and chemical reactions that occur during the pyrolysis of methacrylate-based resin structures, yielding fundamental knowledge and an improved understanding of the pyrolysis processes. Based on our results, the pyrolysis process can be divided into three stages: monomer evaporation, chemical decomposition, and carbonization, in which the volume shrinkage mainly occurs in the first and third stages. The three stages have different effects on the mechanical properties of the pyrolyzed structures, with monomer evaporation and carbonization enhancing the Young's modulus while decomposition reduces the Young's modulus. Additionally, the surface smoothness of the photocured structures can be improved during pyrolysis due to the shrinkage of the polymer resins, which provides a potential approach to generating ultrasmooth carbon surfaces. Graphical abstract: Image 1 Highlights: Two-photon polymerized methacrylate was pyrolyzed under different conditions to reveal the property changes during the pyrolysis. Monomer evaporation/decomposition, bond cleavage, thermal reflow, and carbonization occur during the pyrolysis. Monomer evaporation/decomposition and carbonization enhance the Young's modulus and induce significant shrinkage. Bond cleavage reduces the Young's modulus significantly while barely changes the morphology.